Optimization Conditions of Ultrasound-Assisted Extraction for Phenolic Compounds and Antioxidant Activity from Rubus alceifolius Poir Leaves - Chi Hai Tran; Minh Tri Nghiem; Anh Minh Trinh Dinh; Thi Thuy Nga Dang; Thi Thuy Van Do; Thi Nga Chu; Tien Hung Mai; Van Man Phan (International Journal of Food Science)
Rubus alceifolius Poir (R.A. Poir) leaves are rich in phenolic compounds, offering many health benefits due to their incredible antioxidant potential. In this study, conditions for the ultrasound-assisted extraction (UAE) of phenolic compounds and antioxidant activity from R.A. Poir leaves were optimized using response surface methodology (RSM). This methodology assessed the effects of ultrasound power (X1: 100-500 W), extraction temperature (X2: 30-60°C), and extraction time (X3: 5-55 min). The optimized UAE conditions were then compared with conventional extraction methods (Soxhlet extraction: SE and maceration extraction: ME) for extracting total phenolics. A phenolic profile using GC-MS and antioxidant activity (ABTS) was also compared. According to the RSM, the best conditions for UAE to extract the highest total polyphenol content and ABTS radical scavenging activity were 320 W ultrasound power, 40°C extraction temperature, and 35.5 min sonication duration. Under these optimal conditions, the TPC and antioxidant activity reached 16.68 mg GAE/g dm and 21.9 mg TE/g, respectively, closely aligning with the predicted values. The UAE extraction technique proved to be more efficient in extracting phenolics and antioxidant capacity (ABTS (2,2′-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid)) radical scavenging activity, and enzyme inhibition) compared to the conventional extraction methods (SE and ME). A GC-MS analysis identified 12 components, including 5 phenolics and 3 flavonoids, which likely contribute to the antioxidant activity. Consequently, the UAE method improved extraction efficiency within a shorter time frame, suggesting that UAE is a promising, efficient, and ecofriendly technology for extracting bioactive compounds from R.A. Poir leaves.